(untitled) (Scientific journal of the Fergana State University, 2024)
This article explores the transposition of adjectives in the English language, highlighting the flexibility and adaptability of adjective order beyond the traditional framework. It delves into the cognitive and pragmatic factors that influence adjective placement, emphasizing how speakers and writers prioritize certain attributes to enhance clarity, emphasis, and aesthetic effect. By examining theoretical insights and practical applications, the study underscores the importance of understanding both standard adjective sequences and instances of transposition. This knowledge enriches language teaching and learning, preparing students for real-world communication. The article concludes by suggesting areas for future research, particularly the impact of cultural and contextual influences on adjective order.